Metachronous ovarian cancer metastasis of large bowel presenting similar imaging features of GIST - Taşcı, Halil İbrahim; Erinanc, Hilal; Turk, Emin; Karagülle, Erdal (Journal of Surgery and Medicine, 2022)
Ovarian cancer most likely spreads into the peritoneal cavity or can be only superficially invasive. Although the most common metastatic pathway used by ovarian cancer cells involves peritoneal seeding, hematogenous and lymphatic dissemination can also occur. Metastatic colorectal cancers arising from the ovary are extremely rare. A mass arising from the colon wall at the level of the hepatic flexure was detected by tomography during routine follow-up of a patient who underwent abdominal hysterectomy + bilateral salpingo oophorectomy for ovarian cancer two years ago. Radiological findings revealed that the mass mimicked a gastrointestinal stromal tumor, and the patient underwent surgery based on a pre-diagnosis of gastrointestinal stromal tumor. Pathological examination of the specimen showed that the present mass was an ovarian tumor metastasis. Immunohistochemical staining of the sample was positive for CK7, PAX-8, WT-1, P16, and P53 and was negative for CK20 and CDX-2. A case of gastrointestinal metastasis of ovarian cancer is presented in which the imaging features mimicked a gastrointestinal stromal tumor that appeared two years after the first surgery. Although similar imaging characteristics of these two tumors were present, it was thought that gastrointestinal metastasis of ovarian cancer should be considered first in the differential diagnosis of patients who had history of previous ovarian cancer. The clinical presentation, management, and outcome in that case are discussed.